82.2k views
10 votes
G1(1)=51
g(n)=g(n_1)+2

User Yous
by
5.3k points

1 Answer

7 votes

Answer:


g_n = 49+ 2n

Explanation:

Given


g_1=51


g_n=g_(n-1)+2

Required

Determine the explicit formula (missing from the question)

First, calculate g2


g_n=g_(n-1)+2


g_2 = g_(2-1) +2


g_2 = g_1 +2


g_2 = 51 +2


g_2 = 53

So, we have:


g_1=51


g_2 = 53

Calculate the common difference:


d = g_2 - g_1


d = 53 - 51


d = 2

The explicit formula is calculated using:


g_n = g_1 + (n-1)d

This gives:


g_n = 51 + (n-1)*2


g_n = 51 + 2n-2

Collect Like Terms


g_n = 51 -2+ 2n


g_n = 49+ 2n

User Aureliano Far Suau
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.